The Existence of Mickey Mouse as the Walt Disney Company’s Mascot in the Global Value Chain Perspective - Putri, Syora Alya Eka (UI Scholars Hub, 2019)
This article analyses the existence of Mickey Mouse as the mascot of the Walt Disney Company based on global value chain perspective. As the official mascot of Walt Disney Company, Mickey Mouse has been well-established since 1928 to the present day, its artwork having been produced as motion pictures, television series, comics, books, and theme parks. Its existence has made Walt Disney Company as one of the most successful multinational companies that dominate the entertainment industry in the world. Earlier studies have explained that the existence of a company’s mascot in the entertainment industry is perpetuated by the company’s strategy through branding and supply chain management. However, in the global value chain, previous studies have not yet discussed companies by their mascots, focusing only on the business activities in the industry. Therefore, this article analyses the mascot of the Walt Disney Company: Mickey Mouse,in building the company into the global economy using the global value chain perspective. Nonetheless, the branding strategy and supply chain management correlate to one of the global value chain elements, theinput-output structure. The perpetuation of the existence of a mascot is supported by other global value chain elements, namelythe local institutional context and geographic scope.